2011
DOI: 10.2113/gsjfr.41.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Patchiness on Modern Salt-Marsh Foraminifera Used in Sea-Level Studies (North Carolina, Usa)

Abstract: We collected replicate samples at stations placed systematically along a transect at Oregon Inlet (North Carolina, USA) to investigate spatial homogeneity of dead assemblages of saltmarsh foraminifera. Analysis of variance (ANOVA) was used to investigate the differences in mean proportions for six species (Miliammina fusca, Trochammina inflata, Arenoparrella mexicana, Tiphotrocha comprimata, Haplophragmoides wilberti and Jadammina macrescens) selected because of their importance in distinguishing assemblages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…Within the lowand high-marsh floral zone there was no patchiness of any foraminiferal species. Kemp et al (2011) concluded that "this result supported the validity of our initial assumption of environmental homogeneity in salt-marsh floral zones". Division by cluster analysis of the middle marsh floral zone into two foraminiferal assemblages showed, however, that, while A. mexicana, T. comprimata, H. wilberti and J. macrescens did not have patchy distributions in the middle marsh, M. fusca and T. inflata did.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Within the lowand high-marsh floral zone there was no patchiness of any foraminiferal species. Kemp et al (2011) concluded that "this result supported the validity of our initial assumption of environmental homogeneity in salt-marsh floral zones". Division by cluster analysis of the middle marsh floral zone into two foraminiferal assemblages showed, however, that, while A. mexicana, T. comprimata, H. wilberti and J. macrescens did not have patchy distributions in the middle marsh, M. fusca and T. inflata did.…”
Section: Introductionsupporting
confidence: 70%
“…If changes in the environment are sufficiently large, generalist species will also change in abundance or entirely disappear. Such studies of modern dead assemblages as that by Kemp et al (2011) are comparable to those of fossil communities, which likewise comprise dead specimens. This paper uses the General Linear Model approach to analysis of variance (ANOVA) to test this ontological assumption (sensu regarding relative specialist and generalist species.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The highest occurrence of foraminifera at Placentia was 0.75 m above MTL (PLA-B station 11) and 257 samples above this elevation on all three transects were devoid of foraminifera (Figure 2 among transects (maximum abundance of <5% on BRM-0, but up to 49% on BRM-1 and 37% on 296 BRM-2) as does Trochammina inflata (maximum abundance of 29% on BRM-0, 2.5% of BRM-1 and 6% 297 on BRM-2), which may reflect a patchy distribution (e.g., Kemp et al, 2011, Swallow, 2000 and/or 298 within site variability of secondary environmental factors such as salinity or sediment texture that were 299 not measured. Modern foraminifera data are presented in the supporting appendix.…”
Section: Foraminifera 256mentioning
confidence: 95%
“…In the state of Rio de Janeiro, different works with foraminifera characterize coastal environments (Debenay et al, 1998, Vilela et al, 2004, 2014Uehara et al, 2007, Eichler et al, 2007, Wilson et al, 2008Kemp et al, 2011;Mamo et al, 2013) and its paleo-environmental evolution due to oscillations of sea level (Barbosa et al, 2005;Bruno, 2012;Laut et al, 2012). But in Restinga of Jurubatiba lagoons, few foraminiferal studies have been developed, as this pioneer work will bring contributions for the scientific investigation and for the preservation of this ecosystem.…”
Section: Introductionmentioning
confidence: 99%